Class II malocclusion treatment with twin block and mandibular anterior repositioning appliance: a comparative study of dentoskeletal changes - Bastiani, Cristina (2019)
Background: The aim of this study was to compare the cephalometric changes in patients Class II division 1treated with Twin Block and MARA appliances. Material and Methods: The sample comprised 66 patients with Class II malocclusion divided into 3 groups: The Twin Block group consisted of 21 patients, the MARA group of 21 patients and the control group of 24 untreated subjects. Intergroup comparisons were performed at pre- (T1) and posttreatment (T2) stages. The initial and posttreatment measures concerning changes in angular and linear variables were compared using the analysis of variance (ANOVA) and Kruskal-Wallis tests. Results: Both appliances showed improvement of the relation Class II. MARA resulted in a significant increase in FMA and the occlusal plane, 1º more than control. Twin Block revealed significantly greater increase in LAFH than the others. MARA produced a significantly greater amount of labial tipping and protrusion of the mandibular incisors than the others groups. TB showed significant extrusion of the mandibular incisors compared to MARA and extrusion of the mandibular molars in relation to the control. Both treated groups showed improvement in the overjet, overbite and molar relationship. The treatment time for MARA almost was 1 year less than TB. Conclusion: The appliances were effective in the treatment of Class II malocclusion; however, the correction was mainly due to dentoalveolar effects.